PREPARASI DAN KARAKTERISASI SELULOSA MIKROKRISTAL DARI NATA DE PINA SEBAGAI BAHAN EKSIPIEN DALAM SEDIAAN TABLET - Rum, Ira Adiyati (Journal of Pharmacopolium, 2018)
Microcrystalline cellulose is one of the excipients of the tablet. So far the pharmaceutical industry uses microcrystalline cellulose from synthetic materials, not much development of microcrystalline cellulose from natural materials. Pineapple fruit with abundant availability in Indonesia can be used as a base material in microcrystalline cellulose manufacturing process, pineapple fruit previously processed first into nata de pina. Pineapple fruit can be used as the basic ingredients of nata because pineapple fruit contains carbohydrates, vitamins and water needed in the process of fermentation of pineapple juice by Acetobacter xylinum bacteria. Objective: To find out whether nata de pina can be used as raw material for microcrystalline cellulose manufacture. Find out the characterization of microcrystalline cellulose from nata de pina and compare it with avicel PH 102 Knowing the characterization of tablets using microcrystalline cellulose nata de pina as excipient material. Methodology: Preparation of nata de pina, evaluation of nata de pina, manufacturing of microcrystalline cellulose nata de pina, evaluation of microcrystalline cellulose nata de pina, optimization of furosemide tablet formulations, evaluation of furosemide tablets, comparison test. Result: Nata de pina can be used as raw material in making microcrystalline cellulose. The SEM test shows the existence of size and shape equation between microcrystalline cellulose nata de pina and avicel PH 102. The formula with the best tablet that is the 2nd formula using microcrystalline cellulose nata de pina of 60%, tablet formula 2 has a break time 5,91 minutes With the amount of dissolved furosemide in the 60th minute of 87.20%. Tablets using microcrystalline cellulose nata de pina as 60% concentrates have faster disintegration time and better dissolution profiles than tablets using avicel PH 102 at the same amount. In the dissolution profile comparison test, tablets using avicel PH 102 had a reduced number of furosemides in the 60th minute ie only 86.56%. This is related to the time destroyed tablets avicel PH 102 is longer that is 8.32 minutes.